Structure and Photo-response Properties of FZO/ITO Thin Film - Amrina Mustaqim -; Yeli Krisdayanti Lature; Mohamad Samsul Anrokhi; Koko Friansa; Retno Maharsi; Eka Nurfani (Newton-Maxwell Journal of Physics, 2024)
The structure and photo-response properties of ZnO:Fe/ITO thin film synthesized using  a pyrolysis method were studied in this work. ZnO:Fe/ITO thin film referred to as FZO/ITO was characterized using the X-ray diffraction (XRD) technique and current-voltage (I-V) measurements. The XRD analysis showed that the detected peaks at 30.23°, 35.15°, 37.36°, 45.18°, and 50.54° belonged to the ITO cubic phase. The I-V analyses showed that the sample had the saturation current, Schottky barrier, and sensitivity of 16.24 µA, 0.4771, and 0,90 µA respectively. The FZO/ITO gave a good response toward the light.